Expression profiling of various genes during the fruit development and ripening of mango - Pandit, Sagar S.; Kulkarni, Ram S.; Giri, Ashok P.; Koellner, Tobias G.; Degenhardt, Joerg; Gershenzon, Jonathan; Gupta, Vidya S. (Plant Physiology and Biochemistry, 2010)
Mango (Mangifera indica L. cv. Alphonso) development and ripening are the programmed processes; conventional indices and volatile markers help to determine agronomically important stages of fruit life (fruit-setting, harvesting maturity and ripening climacteric). However, more and precise markers are required to understand this programming; apparently, fruit's transcriptome can be a good source of such markers. Therefore, we isolated 18 genes related to the physiology and biochemistry of the fruit and profiled their expression in developing and ripening fruits, flowers and leaves of mango using relative quantitation PCR. In most of the tissues, genes related to primary metabolism, abiotic stress, ethylene response and protein turnover showed high expression as compared to that of the genes related to flavor production. Metallothionin and/or ethylene-response transcription factor showed highest level of transcript abundance in all the tissues. Expressions of mono- and sesquiterpene synthases and 14-3-3 lowered during ripening; whereas, that of lipoxygenase, ethylene-response factor and ubiquitin-protein ligase increased during ripening. Based on these expression profiles, flower showed better positive correlation with developing and ripening fruits than leaf. Most of the genes showed their least expression on the second day of harvest, suggesting that harvesting signals significantly affect the fruit metabolism. Important stages in the fruit life were clearly indicated by the significant changes in the expression levels of various genes. These indications complemented those from the previous analyses of fruit development, ripening and volatile emission, revealing the harmony between physiological, biochemical and molecular activities of the fruit. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: Mangifera indica; Stress response; Terpene metabolism; Transcriptome analysis

Enhanced permeation, leaf retention, and plant protease inhibitor activity with bicontinuous microemulsions - Tamhane, Vaijayanti A.; Dhaware, Deepika G.; Khandelwal, Neha; Giri, Ashok P.; Panchagnula, Venkateswarlu (Journal of Colloid and Interface Science, 2012)
Bicontinuous microemulsions (BCMEs) have excellent solubulizing properties along with low interfacial tension and aqueous content that can be controlled. In this work, water soluble plant protease inhibitor (PI), well characterized for its activity against insect pests, was incorporated into a BCME system and explored for permeation on hydrophobic leaf surfaces and protease inhibition activity. The bicontinuous nature of the microemulsion containing water:2-propanol:1-butanol (55:35:10 w/w) was characterized using conductivity and self-diffusion coefficient measurements. The PI was soluble in the water-rich bicontinuous domains, stable in the microemulsions, and protease inhibition activity was retained for a prolonged duration. The microemulsions ensured greater wettability and a wider spread of the PI on hydrophobic leaf surfaces as revealed by contact angle measurements. Significantly, trypsin inhibition activity assays of the PI recovered from the leaves after delivery from the microemulsion indicated a significant increase in the PI retention on the leaf. This BCME enabled greater leaf permeation and retention of the PI can be attributed to a temporary disruption of the waxy leaf surface followed by self-repair without causing any long term damage to the plant. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Bicontinuous microemulsion; Biopesticide; Microemulsion pesticide; protease inhibitor; Protein encapsulation; Protein permeation

Ecological turmoil in evolutionary dynamics of plant-insect interactions: defense to offence - Mishra, Manasi; Lomate, Purushottam R.; Joshi, Rakesh S.; Punekar, Sachin A.; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2015)
Available history manifests contemporary diversity that exists in plant-insect interactions. A radical thinking is necessary for developing strategies that can co-opt natural insect-plant mutualism, ecology and environmental safety for crop protection since current agricultural practices can reduce species richness and evenness. The global environmental changes, such as increased temperature, CO (2) and ozone levels, biological invasions, land-use change and habitat fragmentation together play a significant role in re-shaping the plant-insect multi-trophic interactions. Diverse natural products need to be studied and explored for their biological functions as insect pest control agents. In order to assure the success of an integrated pest management strategy, human activities need to be harmonized to minimize the global climate changes. Plant-insect interaction is one of the most primitive and co-evolved associations, often influenced by surrounding changes. In this review, we account the persistence and evolution of plant-insect interactions, with particular focus on the effect of climate change and human interference on these interactions. Plants and insects have been maintaining their existence through a mutual service-resource relationship while defending themselves. We provide a comprehensive catalog of various defense strategies employed by the plants and/or insects. Furthermore, several important factors such as accelerated diversification, imbalance in the mutualism, and chemical arms race between plants and insects as indirect consequences of human practices are highlighted. Inappropriate implementation of several modern agricultural practices has resulted in (i) endangered mutualisms, (ii) pest status and resistance in insects and (iii) ecological instability. Moreover, altered environmental conditions eventually triggered the resetting of plant-insect interactions. Hence, multitrophic approaches that can harmonize human activities and minimize their interference in native plant-insect interactions are needed to maintain natural balance between the existence of plants and insects.
Keywords: Climatic change; Co-evolution; Ecosystem; Human interference; Plant-insect interaction

Expression of proteins involved in digestion and detoxification are regulated in helicoverpa armigera to cope up with chlorpyrifos insecticide - Dawkar, Vishal V.; Chikate, Yojana R.; More, Tushar H.; Gupta, Vidya S.; Giri, Ashok P. (Insect Science, 2016)
Helicoverpa armigera is a key pest in many vital crops, which is mainly controlled by chemical strategies. To manage this pest is becoming challenging due to its ability and evolution of resistance against insecticides. Further, its subsequent spread on nonhost plant is remarkable in recent times. Hence, decoding resistance mechanism against phytochemicals and synthetic insecticides is a major challenge. The present work describes that the digestion, defense and immunity related enzymes are associated with chlorpyrifos resistance in H. armigera. Proteomic analysis of H. armigera gut tissue upon feeding on chlorpyrifos containing diet (CH) and artificial diet (AD) using nano-liquid chromatography-mass spectrometry identified upregulated 23-proteins in CH fed larvae. Database searches combined with gene ontology analysis revealed that the identified gut proteins engrossed in digestion, proteins crucial for immunity, adaptive responses to stress, and detoxification. Biochemical and quantitative real-time polymerase chain reaction analysis of candidate proteins indicated that insects were struggling to get nutrients and energy in presence of CH, while at the same time endeavoring to metabolize chlorpyrifos. Moreover, we proposed a potential processing pathway of chlorpyrifos in H. armigera gut by examining the metabolites using gas chromatography-mass spectrometry. H. armigera exhibit a range of intriguing behavioral, morphological adaptations and resistance to insecticides by regulating expression of proteins involved in digestion and detoxification mechanisms to cope up with chlorpyrifos. In these contexts, as gut is a rich repository of biological information; profound analysis of gut tissues can give clues of detoxification and resistance mechanism in insects.
Keywords: chlorpyrifos; Helicoverpa armigera; insecticide resistance; proteomics; real-time PCR

Effect of postharvest ethylene treatment on sugar content, glycosidase activity and its gene expression in mango fruit - Chidley, Hemangi G.; Deshpande, Ashish B.; Oak, Pranjali S.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Journal of the Science of Food and Agriculture, 2017)
BACKGROUND: Ripening-associated softening is one of the important attributes that largely determines the shelf-life of mango (Mangifera indica Linn.) fruits. To reveal the effect of pre-climacteric ethylene treatment on ripening-related softening of Alphonso mango, ethylene treatment was given to mature, raw Alphonso fruits. Changes in the pool of reducing and non-reducing sugars, enzymatic activity of three glycosidases: ss-D-galactosidase, alpha-D-mannosidase and ss-D-glucosidase and their relative transcript abundance were analysed for control and ethylene treated fruits during ripening. RESULTS: Early activity of all the three glycosidases and accelerated accumulation of reducing and non-reducing sugars on ethylene treatment was evident. ss-D-Galactosidase showed the highest activity among three glycosidases in control fruits and marked increase in activity upon ethylene treatment. This was confirmed by the histochemical assay of its activity in control and ethylene treated ripe fruits. Relative transcript abundance revealed high transcript levels of ss-D-galactosidase in control fruits. Ethylene-treated fruits showed early and remarkable increase in the ss-D-galactosidase transcriptswhile alpha-D-mannosidase transcript variants displayed early accumulation. CONCLUSION: Thefindings suggest reduction in the shelf-life of Alphonso mango upon pre-climacteric ethylene treatment, a significant role of ss-D-galactosidase and alpha-D-mannosidase in the ripening related softening of Alphonso fruits and transcriptional regulation of their expression by ethylene. (C) 2016 Society of Chemical Industry

Effectors of root-knot nematodes: an arsenal for successful parasitism - Jagdale, Shounak; Rao, Uma; Giri, Ashok P. (Frontiers in Plant Science, 2021)
Root-knot nematodes (RKNs) are notorious plant-parasitic nematodes first recorded in 1855 in cucumber plants. They are microscopic, obligate endoparasites that cause severe losses in agriculture and horticulture. They evade plant immunity, hijack the plant cell cycle, and metabolism to modify healthy cells into giant cells (GCs) – RKN feeding sites. RKNs secrete various effector molecules which suppress the plant defence and tamper with plant cellular and molecular biology. These effectors originate mainly from sub-ventral and dorsal oesophageal glands. Recently, a few non-oesophageal gland secreted effectors have been discovered. Effectors are essential for the entry of RKNs in plants, subsequently formation and maintenance of the GCs during the parasitism. In the past two decades, advanced genomic and post-genomic techniques identified many effectors, out of which only a few are well characterized. In this review, we provide molecular and functional details of RKN effectors secreted during parasitism. We list the known effectors and pinpoint their molecular functions. Moreover, we attempt to provide a comprehensive insight into RKN effectors concerning their implications on overall plant and nematode biology. Since effectors are the primary and prime molecular weapons of RKNs to invade the plant, it is imperative to understand their intriguing and complex functions to design counter-strategies against RKN infection.

Engineering inhibitory repeat domains of Pin-II type proteinase inhibitors indicate their high structural-functional tolerance to mutagenesis - Barbole, Ranjit S.; Joshi, Rakesh S.; Giri, Ashok P. (Biochemical and Biophysical Research Communications, 2024)
Plant proteinase inhibitors (PIs) are critical in defending against biotic stress. Most PIs contain an inhibitory repeat domain (IRD), which serves as the functional component, displaying a high degree of sequence and structural conservation. In this study, we examined the structural and functional resilience of IRDs using a combination of computational modeling and experimental validation. We have taken an evolution-based approach to enhance the PIs effectiveness of two previously identified Capsicum annuum IRDs, IRD4 and IRD10. Through in silico site-saturation mutagenesis of IRD4 and IRD10, we identified key sites associated with enhanced PI activity for targeted mutagenesis. Binding energy predictions for a mutant IRD library, tested against target proteases, suggested that positions R11 and N32 in IRD4 and N32 and H33 in IRD10 were promising candidates for further modification to improve inhibitory potential. Subsequent experimental validation revealed that the mutant proteins IRD4_R11K and IRD4_N32S exhibited stronger chymotrypsin inhibition than the wild-type (WT) IRD4. Similarly, the mutants IRD10_N32S and IRD10_H33 N demonstrated improved trypsin inhibition relative to the WT IRD10. These findings indicate that engineered IRD variants can tolerate structural changes while maintaining or enhancing their inhibitory activity against target proteases. Overall, this study demonstrates the potential of engineering PIs to increase their structural and functional resilience, offering new opportunities for biotechnological applications.
Keywords: Capsicum annum; Inhibitory repeat domain; molecular modeling; plant proteinase inhibitors; Proteases; Saturation mutagenesis